"It's just what you do": Australian middle-class heterosexual couples negotiating compulsory parenthood. (August 2018) - Riggs, Damien W; Bartholomaeus, Clare
A distinction is often made between the "choice" of not having children and the claim that having children is "natural". What disappears in this distinction is the fact that having children is most often a choice. This choice, however, is rendered invisible through the naturalisation of parenthood as a normatively expected aspect of adulthood. Whilst this argument is not new, the topic of how heterosexual couples come to decide to have children has received relatively little attention within the academic literature. This paper reports on findings from the first stage of a longitudinal interview study focused on Australian middle-class heterosexual couples planning for a first child. A thematic analysis of interviews conducted with 10 couples found that a paired contrast was often made between what were constructed as "childless others", and a "natural" or "innate" desire to have children. The naturalisation of a desire to have children, however, was problematised when participants spoke about expectations from family members that participants should have children. The paper concludes by considering how the relationship between parenthood and adulthood may be a specifically class-based narrative.